AN INTRODUCTION TO PRACTICAL THEOLOGY: HISTORY, THEORY, AND THE COMMUNICATION OF THE GOSPEL IN THE PRESENT - J Meyer (Acta Theologica)
Juanita Meyer reviews a book of GRETHLEIN, C. (Waco, Texas: Baylor University Press, 2016) 264pp. ISBN: 9781481305174.